COMPUTATIONAL THINKING SKILLS IN MATHEMATICS PROBLEM-SOLVING: A SYSTEMATIC LITERATURE REVIEW - Afidatunisa, Shera; Juandi, Dadang (JURNAL NALAR PENDIDIKAN, 2024)
Computational thinking and Problem-Based Learning have educational benefits for learners and have been widely used in teaching and learning. However, research into integrating these theories into the teaching and learning process is scarce, leaving educators with little guidance in using constructive learning theory techniques. This research aims to thoroughly review and determine the place of research, level, learning materials, type of research, and instruments used to get an overview of how computational thinking, problem-solving, and learning methodologies lead to the successful application of computational thinking and problem-solving. From 2018-2023, this research tracks relevant published articles to identify gaps in implementing computational thinking and problem-solving. Research on computational thinking in problem-solving in the last five years has been widely used, but it still needs to be improved for other researchers, especially in provinces with few or even few researchers. Other researchers, especially in provinces that still have little or no research on computational thinking in problem-solving. have not examined computational thinking in problem-solving. In addition, the material that is taught to support computational thinking is the most widely used number pattern material at the junior high school level with test instruments and interviews.